Exploring Education for Digital Librarians: Meaning, Modes and Models (Chandos Information Professional Series) - Myburgh, Susan (Chandos Publishing, 2013)
Intended for LIS students and faculty, Exploring Education for Digital Libraries offers an overview of the library and e-learning, and presents international perspectives on learning within and preparing for future professional information careers. The book challenges the idea that technology can replace libraries and librarians while contributing to a broader understanding of the role virtual information environments play in LIS. It also explores an innovative model for the skills and knowledge needed in the field. Of special interest is an informative overview of the library and i-School situation.